Africa’s Strategies to Build Supportive Business Environment for Tourism Businesses - Boitumelo Caroline Rasethuntsa (Journal of Business and Management Review, 2021)
The Travel and Tourism Competitive Index regards the business environment as one of the pillars supporting the tourism industry wellbeing. Africa has failed to stay competitive in the global tourism industry since 2007; hence studies that have the potential to positively influence the tourism policies are critical at this point. Although the importance of the business environment has been emphasised, researchers have not been keen to explore this area, especially in the African context. This study aims to create an understanding on the business environment support structures, policies and practices employed by best tourism performing African countries. Using the secondary research approach, the findings of this study shed light on the legal frameworks, taxation policies, public sector institutions, and business policies utilised by the benchmarking countries to enable a supportive business atmosphere. A comparative analysis of strategies practiced by the benchmarking countries is presented to identify the similarities and differences of the strategies implemented in the benchmarking countries.